Some Prospective Alternatives for Treating Pain: The Endocannabinoid System and Its Putative Receptors GPR18 and GPR55 - Guerrero-Alba, Raquel; Barragán-Iglesias, Paulino; González-Hernández, Abimael; Valdez-Moráles, Eduardo E.; Granados-Soto, Vinicio; Condés-Lara, Miguel; Rodríguez, Martín G.; Marichal-Cancino, Bruno A. (Frontiers in Pharmacology, 2019)
Background: Marijuana extracts (cannabinoids) are used since several millennia for pain treatment. Regarding the site of action, cannabinoids are highly promiscuous molecules, but only two cannabinoid receptors (CB1 and CB2) have been deeply studied and classified. Thus, therapeutic actions, side effects and pharmacological targets for cannabinoids have been explained based on the pharmacology of cannabinoid CB1/CB2 receptors. However, the accumulation of confusing and sometimes contradictory results suggests the existence of other cannabinoid receptors. Different orphan proteins (e.g., GPR18, GPR55, GPR119, etc.) have been proposed as putative cannabinoid receptors. According to their expression, GPR18 and GPR55 could be involved in sensory transmission and pain integration. Methods: This article reviews select relevant information about the potential role of GPR18 and GPR55 in the pathophysiology of pain. Results: This work summarized novel data supporting that, besides cannabinoid type-1 (CB1) and cannabinoid type-2 (CB2) receptors, GPR18 and GPR55 may be useful for pain treatment. Conclusion: There is evidence to support an antinociceptive role for GPR18 and GPR55.